Development and Validation of a Red Flag Prediction Model for Admission of COVID-19 Patients to the Intensive Care Unit. Issue 2 (April 2023) - Mahran, Ghada S. K.; Gadallah, Marzoka A.; Mekkawy, Mimi M.; Ahmed, Sanaa M.; Sayed, Magdy M. M.; Obiedallah, Ahmed A.; Abbas, Mostafa S.; Mohamed, Sherif A. A.
Abstract : We aimed to develop and validate a model for the criteria for admission of COVID-19 patients to the intensive care unit (ICU). A Delphi design study was conducted. The content validity index (CVI) was used to determine the degree of agreement among the experts to validate the content of the admission criteria tool. Eleven experts determined the validity. The evaluation was conducted using a 4-point rating scale. The accepted CVI value was 0.50 and more. The model was validated with 31 items in the 5 dimensions, with the item-CVI of 1, a face validity index of 1, and a scale-level content validity index (S-CVI) value of 1. We have developed and validated a red flag prediction model for ICU admission of COVID-19 patients. The accurate implementation of this model could improve the outcomes of those patients and possibly decrease mortality.